2019
DOI: 10.3892/ol.2019.9926
|View full text |Cite
|
Sign up to set email alerts
|

Stilbenes contribute to the anticancer effects of Rheum�undulatum L. through activation of apoptosis

Abstract: Rheum undulatum L. (R. undulatum) is a medicinal plant used for the treatment of inflammatory diseases in East Asian countries. Numerous stilbenes isolated from R. undulatum have been revealed to possess anticancer effects. The aim of the present study was to evaluate the effect of extracts and compounds isolated from R. undulatum on human gastric cancer cell viability and to elucidate their molecular mechanism of action on the apoptosis pathway. The results demonstrated that aloe-emodin and chrysophanol 1-O-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Trinh stated that aloe-emodin, chrysophanol, rhapontigenin, and rhaponticin were isolated from the RU extracts and their fractions [ 23 ]. Nevertheless, our study identified chrysophanol, emodin, and physcion to be the major compounds in the RU extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Trinh stated that aloe-emodin, chrysophanol, rhapontigenin, and rhaponticin were isolated from the RU extracts and their fractions [ 23 ]. Nevertheless, our study identified chrysophanol, emodin, and physcion to be the major compounds in the RU extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of these cells to aloe-emodin or chrysophanol 1-O-b-D-glucopyranoside increased the poly(ADP-ribose)polymerase (PARP) cleavage and induced downregulation of the anti-apoptotic protein, Bcl-2. Additionally, chrysophanol 1-O-b-D-glucopyranoside slightly stimulated the expression of proapoptotic proteins such as Bid and Bax (Trinh et al 2019). In the MCF-7 human breast cell line, aloeemodin and rhapontigenin induced the mitochondriaindependent apoptosis (mediated by the caspase-8 pathway), while chrysophanol 1-O-b-D-glucopyranoside, acted by the mitochondria-dependent apoptotic pathway (Lee et al 2018).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Տերևակոթունները պարունակում են մինչև 4,5% ածխաջրեր, 3,5% օրգանական թթուներ (խնձորաթթու, օքսալաթթու, կիտրոնաթթու), անտրաքինոններ, անտրոններ, ստիլբեններ, ֆլավոնոիդներ, գլիկոզիդներ, դաբաղանյութեր, վիտամիններ, β-կարոտին, կալիում, կալցիում, ֆոսֆոր, սելեն, մագնեզիում և այլն [7,10,13,16,21]:…”
Section: Rheum Rhabarbarum Lsoilless Culturemonosaccharidesoxalic Acidunclassified
“…Խավրծիլը հայտնի է ասիական, եվրոպական և այլ մշակույթների ավանդական բժշկության [4], այուվերդյան բժշկության մեջ [9], իսկ Իրանում կիրառվում է մաշկի գերպիգմենտացիայի բուժման ժամանակ [11]: Այն ունի հիպոլիպիդեմիկ ազդեցություն, օգտագործվում է ճարպակալման դեմ, նաև հակաքաղցկեղածին է [17,21]:…”
Section: Rheum Rhabarbarum Lsoilless Culturemonosaccharidesoxalic Acidunclassified